1993
DOI: 10.1007/bf00295196
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic effects of extracorporeal shock wave lithotripsy on rabbit kidney

Abstract: Despite the widespread clinical use of the lithotriptor, the margin of safety for the kidney during shock wave application is substantially unknown. Although a series of pilot studies have been performed in laboratory animals, long-term follow-up is mandatory to establish the effect of extracorporeal shock wave lithotripsy (ESWL) and subsequent dose-dependent changes on the kidneys. An experimental study was performed in 45 rabbits; to define and compare the early and late complications of ESWL in the kidneys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The vast majority of studies show that SW cause renal damage, but there is a broad spectrum to the severity of injury described in this literature. Earlier studies in dogs showed minimal-or-no injury [9], while more recent work with dogs [10, 11, 12, 13, 14, 15, 16], rats [17, 18], pigs [19, 20, 21, 22, 23], and rabbits [24, 25] demonstrated substantial morphologic and functional alterations following SWL. These apparent contradictions resolve when one recognizes that the kidney is sensitive to the dose of SW insult (i.e., number of SWs, SW voltage, rate of SW administration) [11, 14, 16, 26] and that the magnitude of SW injury is dependent on the size of the kidney [27].…”
Section: Sw Trauma In Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of studies show that SW cause renal damage, but there is a broad spectrum to the severity of injury described in this literature. Earlier studies in dogs showed minimal-or-no injury [9], while more recent work with dogs [10, 11, 12, 13, 14, 15, 16], rats [17, 18], pigs [19, 20, 21, 22, 23], and rabbits [24, 25] demonstrated substantial morphologic and functional alterations following SWL. These apparent contradictions resolve when one recognizes that the kidney is sensitive to the dose of SW insult (i.e., number of SWs, SW voltage, rate of SW administration) [11, 14, 16, 26] and that the magnitude of SW injury is dependent on the size of the kidney [27].…”
Section: Sw Trauma In Experimental Animalsmentioning
confidence: 99%
“…In the pig we see neutrophils, macrophages, and platelets lining injured vessels and within the perivascular and peritubular interstitium as early as 30 min following a clinical dose of SW. The literature suggests that inflammation is a consistent feature of SWL injury when the kidney is treated with a clinical dose of SW [2, 10, 11, 13, 24, 25, 32, 33, 34], but may be absent or minimal in extent at lower, subclinical SW doses [9]. Since inflammation is intimately involved in directing tissue repair toward fibrogenesis and scar formation [35] this may explain why some animal studies of SWL-induced injury have shown limited or no scar formation.…”
Section: ‘Lithotripsy Nephritis’ and Progression To Long-term Complicmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of detrimental effects after intense ESWL applications has been confirmed in many studies. [26,27] Stoller et al [28] retrospectively reviewed their cases and showed that previous ESWL history had no effect on bleeding in subsequent PCNLs.…”
Section: Discussionmentioning
confidence: 99%
“…The traumatic lesions caused by SWL have been studied in human kidneys (Kaude et al, 1985;Brewer et al, 1988;Rigatti et al, 1989;Umekawa et al, 1992;Lechevallier et al, 1993;Roessler et al, 1993) and in animal models, such as the dog (Newman et al, 1987;Abrahams et al, 1988;Delius et al, 1988;Jaeger et al, 1988;Karlsen et al, 1991;Rassweiler et al, 1993;Koga et al, 1996), rat (Neuerburg et al, 1989;Recker et al, 1989;Weber et al, 1992), rabbit (Fajardo et al, 1990;Kaji et al, 1991;Karalezli et al, 1993), and pig (Banner et al, 1991;El-Damanhoury et al, 1991;Evan et al, 1998;Connors et al, 2000). The majority of these studies documented extensive damage to blood vessels in the path of the shock waves, and suggested that the primary injury occurs in vascular tissue.…”
mentioning
confidence: 99%